Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I want to find the inverse of the matrix $A$ given by:

$ \left( \begin{array}{cc} 1 & -\epsilon \\ \epsilon & 1 \\ \end{array} \right) $

where $|\epsilon|$ $< 1$ (although I do not know how to use this yet)

by finding the matrix $B$ such that $A = I-B$ or $B = I-A$.

$B$ is

$ \left( \begin{array}{cc} 0 & \epsilon \\ -\epsilon & 0 \\ \end{array} \right) $

And I want to find the inverse by summing the series $I + B + B^2 + B^3 . . .$

this series doesn't converge (unless we use the fact about the absolute value given, but I don't know what to do with that here).

share|cite|improve this question
up vote 4 down vote accepted

Notice that $$B^2=-\epsilon^2 I$$ so we find easily that $$B^{2p}=(-1)^p\epsilon^{2p}I$$ and $$B^{2p+1}=(-1)^p\epsilon^{2p}B$$ hence $$\sum_{k=0}^\infty B^k=\sum_{p=0}^\infty B^{2p}+\sum_{p=0}^\infty B^{2p+1}=\left(\sum_{p=0}^\infty (-1)^p\epsilon^{2p}\right)I+\left(\sum_{p=0}^\infty (-1)^p\epsilon^{2p}\right)B\\=\frac{1}{1+\epsilon^2}(I+B)$$ Now since $$A\sum_{k=0}^\infty B^k=(I-B)\sum_{k=0}^\infty B^k=I$$ then $$A^{-1}=\frac{1}{1+\epsilon^2}(I+B)$$

share|cite|improve this answer
thanks so much! – terrible at math Feb 21 '14 at 18:00
You're welcome! – user63181 Feb 21 '14 at 18:22

The basic idea, as demonstrated by Sami Ben Romdhane, is convergence of the series $\sum^\infty_{k=0}B^k$.

It's no coincidence that this kind of series gives rise to an inverse. Remember the geometric series? For $q \in \mathbb{C}$ with $\vert q \vert < 1$ we have that $$\sum^\infty_{k=0}q^k=\frac{1}{1-q}.$$

The operator-theoretic equivalent is the Neumann series: If $B$ is some square matrix and the series $\sum^\infty_{k=0}B^k$ converges (w.r.t. some matrix norm), then we have $$\sum^\infty_{k=0}B^k = (I - B)^{-1}.$$

Sami Ben Romdhane's answer has shown this convergence and equality by hand, but you could also use the fact that $\Vert B \Vert_{2,2} = \epsilon <1$ (since the eigenvalues of $B$ are $\pm i \epsilon$).

share|cite|improve this answer

Yet another approach, not really based on series expressing $A^{-1}$ as a polynomial in $A$:

If the $n\times n$ matrix $A$ is non-singular, then you can find an expression for $A^{-1}$ in terms of the powers $A^i$, $i=1,\ldots,n-1$, by using the characteristic polynomial $p$ of $A$. Since $A$ is non-singular, the characteristic polynomial $$ p(t)=t^n+\alpha_{n-1}t^{n-1}+\cdots+\alpha_2t^2+\alpha_1 t + \alpha_0 $$ is such that $\alpha_0\neq 0$. We know that $p$ annihilates $A$: $p(A)=0$, hence $$ p(A)=A^{n}+\alpha_{n-1}A^{n-1}+\cdots+\alpha_2t^2+\alpha_1 A+\alpha_0 I=0. $$ Therefore, $$ A^{n-1}+\alpha_{n-1}A^{n-2}+\cdots+\alpha_2A+\alpha_1 I+\alpha_0 A^{-1}=0 $$ and $$ A^{-1}=-\frac{1}{\alpha_0}\left(A^{n-1}+\alpha_{n-1}A^{n-2}+\cdots+\alpha_2A+\alpha_1 I\right). $$

In your case, $p(t)=t^2-2t+1+\epsilon^2$, so $$ A^{-1}=-\frac{1}{1+\epsilon^2}(A-2I). $$ If $A=I-B$, then $$ A^{-1}=\frac{1}{1+\epsilon^2}(I+B). $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.